Pengaruh Program Lingkungan Bahasa Terhadap Keterampilan Bahasa Arab Pada Anak Didik di Diniyah Takmiliyah Awaliyah - Mochammad Farizky Al Ghazali; Callula Syifa Gantari; Zahra Nabila Yusuf; Eka Cahyani; Ahmad Fu’adin (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This research uses the application of behavioristic learning methods as a way to build an Arabic language environmental program located at Diniyyah Takmiliyyah Awaliyyah. This program has a learning system that has a duration of 2 weeks and involves 20 students. This program applies 4 maharah namely; 1.) listening (al-istimia'), 2.) speaking (al-kalam), 3.) reading (al-qiro'ah), 4.) writing (al-kitabah). This behavioristic method focuses on students showing improvements in terms of attitudes and cognitive qualities that have been studied previously. The language environment can be referred to as external and internal factors in language development. Because the language environment encourages students to apply what they have learned about Arabic. In the pre-program percentage, all students had a percentage of 5% out of 100%, and there was an increase during the course of the program in the 1st week by 10 percent and in the 2nd week by 40%. The results of the research show that the language environment accompanied by the application of behavioristic learning methods influences the improvement of the language skills of Diniyah Takmiliyah Awaliyah students.